청년은 정보 활용격차에서 자유로운가? - 한국 2030 청년세대의 모바일 정보 활용에 관한 연구 - 김설인(Seolihn Kim); 구혜경(Hye-Gyoung Koo) (한국콘텐츠학회 논문지, 21(1), 2021)
This study aim to demonstrate and categorize the status of level of mobile information utilization of the 2030 youth generation, and to identify factors that may affect the digital divide within the generation. For this purpose, 1779 data were analyzed using materials for the 2018 digital divide survey in Korea Ministry of Science and ICT. According to the level of information utilization, the consumers were categorized into three types : reference group (46.5%), high utilization group (27.2%), and low utilization group (26.3%). There were statistically significant differences in demographics variable, consumer capabilities, living satisfaction by type of consumer. In addition, the factors influencing the digital divide of the high utilization group and low utilization group were identified compared to the reference group. It is meaningful that this study confirmed the actual gap of information utilization and raised the possibility of the digital divide within the 2030 youth generation. 본 연구는 2030 청년세대의 모바일 정보 활용수준에 따라 집단을 유형화하고, 유형별 소비자역량과 생활 만족도에 차이가 있는지 실증하고자 하였다. 그리고 세대 내 정보격차에 영향을 미칠 수 있는 요인을 파악하고 자 하였다. 이를 위해 2018년 디지털 정보격차 실태조사 원자료를 활용하여 총 1779부의 유효데이터를 분석하였다. 연구결과, 2030 청년세대의 정보 활용요인은 '개인의 정보활동', '공유활동', '생활서비스', '사회참여', '정보 및 네트워킹', '경제활동'으로 도출되었다. 정보 활용수준에 따라 소비자는 준거집단(46.5%), 고활용집단(27.2), 저활용집단(26.3%) 3가지로 유형화되었으며, 유형별 인구통계학적 특성, 소비자역량, 생활 만족도에서 통계적으로 유의한 차이가 있었다. 그리고 준거집단과 비교하여, 고활용집단과 저활용집단의 정보격차에 영향을 미칠 수 있는 요인을 확인하였다. 본 연구는 2030 청년세대 내 정보 활용수준이 유의한 차이가 있음을 확인하고, 이러한 차이가 정보격차로 이어질 가능성을 피력하였다는 것에 의의가 있다. 청년세대 역시 정보격차의 대상이 될 수 있으며, 향후 정책이나 교육에서도 청년세대 정보격차에 대한 발전된 차원의 논의가 필요할 것이다.